Case report: Thyroid metastasis from hepatocellular carcinoma: a rare case with diffuse solid occupancy and unusual imaging findings - Feng, Tinghua; Xue, Menghua; Sang, Miaoyu; Cui, Rongrong; Liu, Xiaofang; Liu, Liping (Frontiers in Oncology, 2024)
Background Thyroid metastasis represents a rare occurrence, with commonly observed primary tumors originating from renal cell carcinoma, malignant neoplasms of the gastrointestinal tract, lungs, and breast. However, the metastasis of hepatocellular carcinoma to the thyroid gland remains infrequent. Previous investigations have consistently demonstrated an unfavorable prognosis for patients with malignancies that have metastasized to the thyroid. In this context, we present a noteworthy case of thyroid metastasis from hepatocellular carcinoma (HCC), characterized by a distinct ultrasonographic manifestation of diffuse thyroid lesion, deviating from the previously documented imaging presentations of thyroid metastases in HCC. Case presentation A 62-year-old Chinese female patient was diagnosed with hepatocellular liver cancer in 2019, following which she underwent a radical hepatic resection. Pathological examination revealed HCC located in the right lobe (stage T3bN0M0 IIIB). No additional interventions were administered subsequent to the surgery. After a span of 15 months, the patient presented with dyspnea. Ultrasonographic findings showed diffuse solid infiltration within the thyroid gland, along with tumor thrombi in both internal jugular veins. Computed tomography (CT) scans demonstrated malignant thyroid lesions infiltrating the retropharyngeal space, prevertebral space, and esophageal wall. The subsequent pathology report from the puncture biopsy confirmed the malignant nature of the tumor, and immunohistochemical analysis definitively established its hepatic origin. Conclusions Patients with a history of HCC should be subjected to long-term monitoring and habitual thyroid ultrasonography. Newly detected thyroid nodules in such patients should be immediately regarded suspect for potential metastatic disease. Even when a nodule doesn’t exhibit malignant characteristics on ultrasound, FNAB should be administered promptly to elucidate the pathological condition. Larger, swiftly multiplying thyroid masses should warrant an immediate CNB. The identification of thyroid metastases, particularly when coupled with peripheral tissue invasion, typically signifies a bleak prognosis.